Принципы энергосберегающего управления ТЕЦ - Бабенко, Игорь Анатольевич; Сук, Ирина Валентиновна; Сердюк, Александр Викторович; Козлова, Марина Леонидовна (НТУ "ХПИ", 2016)
В настоящей работе рассмотрены общие принципы и основные этапы создания энергосберегающих автоматизированных систем управления технологическим процессом (АСУ ТП) ТЭЦ. Сформулированы общие принципы создания автоматизированных систем управления и на их основе построены математические модели элементов ТЭЦ. Сформулированы общие принципы создания энергосберегающих систем автоматического управления (САУ) основными энергетическими установками ТЭЦ, выявлены определяющие параметры управляющего воздействия, выходные параметры, параметры внешних возмущающих воздействий и параметры энергетических потерь.

The power engineering in Ukraine, in particular heat power engineering comes forth with many solutions that would allow us to improve operating conditions of power plants, namely update the equipment, improve the quality of control of operating conditions depending on power engineering market conditions and update control systems due to the implementation of new computing software systems into the available equipment. Due to the fact that a major portion of the equipment of operating heat power plants is overage and is unable to operate at maximum loadings the approaches to the principles of its control must be revised. This will allow us to reduce the expenditures required for the production of wanted power and optimize the operating conditions of power equipment used by power – generating units of heat power plants. This scientific paper formulates a very important scientific and engineering problem related to the development of the energy-saving control systems for heat power plants. A scientific principle of the energy-saving control of energy-generating units used by heat power plants was formulated, based on which energy-saving systems can be created for the automated control systems of heat power plants. To improve the control property it is proposed to use master models (state viewers) for the energy-saving automated control systems designed for the power-generating units of heat power plants.
Principles of the energy-saving control of heat power plants
Keywords: математические модели; АСУ; энергетика; теплоэлектроцентраль; mathematical models; automated control systems